Field performance of new cowpea cultivars inoculated with efficient nitrogen‑fixing rhizobial strains in the Brazilian Semiarid - Marinho, Rita de Cássia Nunes; Nóbrega, Rafaela Simão Abrahão; Zilli, Jerri Édson; Xavier, Gustavo Ribeiro; Santos, Carlos Antônio Fernandes; Aidar, Saulo de Tarso; Martins, Lindete Míria Vieira; Fernandes Júnior, Paulo Ivan (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the contribution of efficient nitrogen‑fixing rhizobial strains to grain yield of new cowpea cultivars, indicated for cultivation in the Brazilian Semiarid region, in the sub‑medium of the São Francisco River Valley. Two experiments were set up at the irrigated perimeters of Mandacaru (Juazeiro, state of Bahia) and Bebedouro (Petrolina, state of Pernambuco). The treatments consisted of single inoculation of five rhizobial strains – BR 3267, BR 3262, INPA 03‑11B, UFLA 03‑84 (Bradyrhizobium sp.), and BR 3299T (Microvirga vignae) –, besides a treatment with nitrogen and a control without inoculation or N application. The following cowpea cultivars were evaluated: BRS Pujante, BRS Tapaihum, BRS Carijó, and BRS Acauã. A randomized complete block design, with four replicates, was used. Inoculated plants showed similar grain yield to the one observed with plants fertilized with 80 kg ha‑1 N. The cultivars BRS Tapaihum and BRS Pujante stood out in grain yield and protein contents when inoculated, showing their potential for cultivation in the sub‑medium of the São Francisco River Valley.